Interplay of lncRNA H19/miR‐675 and lncRNA NEAT1/miR‐204 in breast cancer - Volkmar Müller; Leticia Oliveira‐Ferrer; Bettina Steinbach; Klaus Pantel; Heidi Schwarzenbach (Molecular Oncology)
Long noncoding RNAs (lncRNAs) are frequently precursor RNAs of microRNAs (miRNAs) or act as competing endogenous RNAs (ceRNAs) to interact with miRNAs. To better understand the shared impact of lncRNAs and miRNAs in the regulatory post‐transcriptional network, we focused here on the relationships between (a) lncRNA H19 and miR‐675, (b) NEAT1 and miR‐204, and (c) HOTAIR and miR‐331 in plasma of early breast cancer (BC) patients. We quantified each RNA in plasma samples of 63 BC patients and 10 healthy women by quantitative real‐time PCR. In cell culture experiments, the influence of these noncoding RNAs (ncRNAs) on proliferation and apoptosis of BC cell line MCF‐7 was examined. Plasma levels of H19 (P = 0.030), NEAT1 (P = 0.030), and miR‐331 (P = 0.012) were deregulated in BC patients compared with healthy women. In both cohorts, the concentrations of H19 correlated with those of miR‐675 (P = 0.0001). Higher H19 (P = 0.001) along with lower miR‐675 (P = 0.007) levels and higher miR‐204 (P = 0.017) along with lower NEAT1 (P = 0.030) levels were detected in plasma of HER2‐positive patients compared with the other BC subgroups. Whereas the expression of HOTAIR was below the detection level, miR‐331 levels correlated with nodal status (P = 0.002) and recurrence (P = 0.012). In cell culture experiments, a competitive impact on cell proliferation and apoptosis by these ncRNAs was also documented. Our findings describe a relationship of the plasma levels of H19/miR‐675 and NEAT1/miR‐204 in the different BC subtypes; in addition, they reveal an interplay between these lncRNAs and miRNAs in the regulatory network in MCF‐7 cells, which should also be considered in the search for new diagnostic and therapeutic markers.